2022
DOI: 10.2174/1566524021666210218113928
|View full text |Cite
|
Sign up to set email alerts
|

Possible Therapeutic Uses of Extracellular Vesicles for Reversion of Activated Hepatic Stellate Cells: Context and Future Perspectives

Abstract: : Liver fibrosis is one of the leading causes for cirrhotic liver disease and the lack of therapies to treat fibrotic liver is a major concern. Liver fibrosis is mainly occurred by activation of hepatic stellate cells and some stem cell therapies had previously reported for treatment. However, due to some problems with cell-based treatment, a safe therapeutic agent is vehemently sought by the researchers. Extracellular vesicles are cell-derived nanoparticles that are employed in several therapeutic approaches,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A comparative proteomic analysis of mouse HSC-derived EVs indicated that EVs from HSCs may play a key role in the regulation of HSC function and activation in vivo [43]. The internalization of hepatocyte-derived EVs by HSCs is dependent on the presence of either vanin-1 (VNN-1) or fibronectin (FN) [43,50,51]. Once internalized, these EVs stimulate the expression of pro-fibrotic mediators in HSCs, as also observed in our studies: hypoxic, palmitate-treated HepG2 cells release EVs that increase the expression of transforming growth factor-β (TGF-β), connective tissue growth factor (CCN2), collagen type 1 and α-smooth muscle actin (α-SMA) in HSCs [43,52].…”
Section: Evs Released From Non-parenchymal Liver Cells In Mafldmentioning
confidence: 99%
“…A comparative proteomic analysis of mouse HSC-derived EVs indicated that EVs from HSCs may play a key role in the regulation of HSC function and activation in vivo [43]. The internalization of hepatocyte-derived EVs by HSCs is dependent on the presence of either vanin-1 (VNN-1) or fibronectin (FN) [43,50,51]. Once internalized, these EVs stimulate the expression of pro-fibrotic mediators in HSCs, as also observed in our studies: hypoxic, palmitate-treated HepG2 cells release EVs that increase the expression of transforming growth factor-β (TGF-β), connective tissue growth factor (CCN2), collagen type 1 and α-smooth muscle actin (α-SMA) in HSCs [43,52].…”
Section: Evs Released From Non-parenchymal Liver Cells In Mafldmentioning
confidence: 99%